Pengaruh Terapi Spiritual Emotional Freedom Technique dan Aromaterapi Lavender Terhadap Penurunan Nyeri Pada Pasien Post Sectio Caesarea di RSU Nurhayati Garut Tahun 2025 - Sumilawati, Euis; Karubuy, Milka Anggraeni; Apriyani, Magdalena Tri Putri (Innovative: Journal Of Social Science Research, 2025)
Post-CS pain is pain caused by incisions in the abdominal wall and uterus. The incidence of CS at Nurhayati Garut Hospital in 2023, around 320 patients and experienced moderate to severe pain. SEFT therapy and lavender aromatherapy are non-pharmacological methods to reduce pain. This study aims to compare the effect of SEFT therapy and lavender aromatherapy on reducing pain in post-CS patients. This study used a quasi-experimental design with a pretest-posttest two group design approach. A sample of 36 post-CS patients using a purposive sampling technique. The pain measurement instrument used the Numerical Rating Scale (NRS). The results of the study showed that the administration of SEFT therapy and lavender aromatherapy had an effect on reducing pain. The results of the paired t-test and independent t-test statistical tests obtained a p value = 0.009 (p <0.05) meaning that there was a difference in the effect between the administration of SEFT therapy and lavender aromatherapy where the administration of SEFT therapy had a greater effect on reducing post-CS pain than lavender aromatherapy. Suggestions, hospitals can consider implementing SEFT therapy as part of non-pharmacological pain management for post-CS patients